The Theatre Criticism of George Stewart, Jr. - Fullerton, Carol W. (Theatre Research in Canada / Recherches théâtrales au Canada, 1988)
George Stewart, Jr. was a conservative theatre critic who published drama reviews over a forty-year period in later nineteenth-century Canada. He was typical of his time in preferring legitimate theatre and the plays of Shakespeare, Sheridan and Goldsmith, as well as in looking for naturalness in an actor or actress. Stewart was an early advocate of the need for critical autonomy, and was active in supporting French- as well as English-Canadian theatre. George Stewart, Jr. fut un critique dramatique conservateur qui sur une période de quelque quarante ans recensait les productions théâtrales du Canada durant la seconde moitié du XIXe siècle. Typique de son époque quant à la préférence qu'il accordait au théâtre légitime, il appréciait surtout l'oeuvre de Shakespeare, Sheridan et Goldsmith, préconisant toujours le jeu naturel des interprètes tout en favorisant la naissance d'un théâtre et d'une critique théâtrale autonomes pour le Canada tant anglais que français.